RANCANG BANGUN SISTEM FILLING SUSU FULL CREAM DAN SUSU KENTAL MANIS OTOMATIS BERBASIS MIKROKONTROLER - Listiana, Reni Listiana; S, Raden Raihan; Wibowo, Santosa Edy; Kurnia, Ahmad (UPPM Politeknik TEDC Bandung, 2025)
Filling system technology is a technology for filling liquid into cups continuously which will make it easier for companies or small entrepreneurs to make drinks. In this technology, an Arduino Atmega 2560 microcontroller is needed as a system control, and an InfraRed (IR) sensor to detect the presence of an object (cup). This filling system technology is used continuously, using a conveyor as a tool to move objects from one place to another. The transfer of the place must have a fixed location so that the conveyor system has economic value. From this filling system, it achieved a success rate of 95% overall, while for sensor accuracy, it was obtained as much as 88% of the 20 cups that had been tested. While for filling milk in 10 cups, the average result was obtained on the first pump, which was 37.5 ml, and on the second pump, which was 49 ml.